HUBUNGAN STRES DAN POLA MAKAN DENGAN KEJADIAN DISPEPSIA - Rahmah, Lestari; Majiding, Chaidir Masyhuri; Alza, Yessi; Ash Siddiq, Muhammad Nuzul Azhim; Mudhofar, Muhamad Nor (Ensiklopedia of Journal, 2024)
Puskesmas Kampar Kiri Tengah is one of the health centers in the working area of the Kampar Regency Health Office which has an increase in the incidence of dyspepsia from 2019 to 2020, namely from 100 cases to 364 cases and dyspepsia disease ranks fifth out of the ten most common diseases at the Puskesmas. The purpose of the study was to determine the relationship between stress and diet with the incidence of dyspepsia. The research method used a cross sectional research design. The population in this study were all patients who visited the Kampar Kiri Tengah Health Center, Kampar Regency in the period January to June 2021, totaling 355 people with a sample of 78 people. The data collection technique used purposive sampling. The research instrument used a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between stress levels (p value: 0.001) and diet (p value: 0.000) with the incidence of dyspepsia. It is suggested that dyspepsia sufferers should prevent dyspepsia starting from maintaining a proper diet. The amount is in accordance with the needs, the type is also diverse, equipped with a regular schedule. In accordance with what is summarized in the 3 right movement (right time, right nutrition and right solution) and for Puskesmas to be able to maintain and improve the quality of existing health services by always conducting counseling on how to prevent dyspepsia.Keywords: Dyspepsia, Stress Level, Diet